2019
DOI: 10.1007/978-3-030-26807-7_8
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Programmable Matter Systems Using Active Tile-Based Self-Assembly

Abstract: Self-assembly refers to the process by which small, simple components mix and combine to form complex structures using only local interactions. Designed as a hybrid between tile assembly models and cellular automata, the Tile Automata (TA) model was recently introduced as a platform to help study connections between various models of self-assembly. However, in this paper we present a result in which we use TA to simulate arbitrary systems within the amoebot model, a theoretical model of programmable matter in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…While the table is still missing a few entries, our contributions have brought the number of known entries up to 52 from the 16 which previously existed in published literature (8 of which were technically not explicitly stated, but were trivial observations based on the tile sets and proofs presented in [7]). 1 The rest of our paper is laid out as follows. In Section 2, we provide definitions of the various models and concepts used.…”
Section: Our Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While the table is still missing a few entries, our contributions have brought the number of known entries up to 52 from the 16 which previously existed in published literature (8 of which were technically not explicitly stated, but were trivial observations based on the tile sets and proofs presented in [7]). 1 The rest of our paper is laid out as follows. In Section 2, we provide definitions of the various models and concepts used.…”
Section: Our Resultsmentioning
confidence: 99%
“…Definition 3. We say that S models T (under R), and we write S |= R T , if for every α ∈ A[T ], there exists Π ⊂ A[S] where Π = ∅ and R * (α ) = α for all α ∈ Π, such that, for every β ∈ A[T ] where α → T β, (1) for every α ∈ Π there exists β ∈ A[S] where R * (β ) = β and α → S β , and (2) for every α ∈ A[S] where α → S β , β ∈ A[S], R * (α ) = α, and R * (β ) = β, there exists α ∈ Π such that α → S α . Definition 4.…”
Section: Formal Definition Of Simulationmentioning
confidence: 99%
“…The authors showed that freezing tile automata (where a tile cannot repeat states) is capable of simulating non-freezing systems. This powerful model has also been shown to be capable of simulating models of programmable matter (Alumbaugh et al 2019). A model motivated by real-world implementations, the Signalpassing Tile Assembly Model, is able to simulate Tile Automata (Cantu et al 2020) meaning results shown in the TA model carry over to STAM at scale.…”
Section: Previous Workmentioning
confidence: 99%
“…By abstracting away implementation details, TA strives to serve as a proving ground for exploring the power of active algorithmic self-assembly, along with providing a central hub through which various disparate models of selfassembly can be related by way of comparison to TA. One example of this type of application includes (Alumbaugh et al 2019) in which TA is shown capable of simulating the Amoebots model (Daymude et al 2019) of programmable matter. More recently a connection between the STAM and Tile Automata was established in (Cantu et al 2020) where it was shown that the STAM is capable of simulating any Tile Automata system.…”
Section: Introductionmentioning
confidence: 99%
“…168 Similar modeling strategies have been used to design, program, and optimize the algorithmically directed assembly of DNA origami tiles. 169,170,187,188 A wide variety of DNA origami tile shapes and interactions are possible, 171 offering ways to build large, complex assemblies with nanoscale resolution. Experimentally implemented systems have been regulated by diverse physical processes, including hybridization, 172 strand displacement, 173 shape complementarity, 171,174 and base stacking.…”
Section: ■ Introductionmentioning
confidence: 99%